RISK ASSESSMENT OF THE HIGHWAY EQUIPPED WITH PROTECTIVE ENGINEERING STRUCTURES - Khvorost, M.; Danova, K.; Malysheva, V.; Хворост, Н. В.; Данова, К. В.; Малышева, В. В.; Хворост, М. В.; Малишева, В. В. (Харьковский национальный автомобильно-дорожный университет, 2016)
The problem of risk assessment of a highway section, which is equipped with protective en-gineering structures to reduce the ingredient-parametric pollution in the dwelling zone is considered, and the methodology of risk assessment «Failure Mode and Effects Analysis» (FMEA) is used to estimate the priority areas of increasing the level of safety in exploitation of the highway equipped with the protective screen.
ОЦЕНКА ОПАСНОСТИ АВТОМОБИЛЬНОЙ ДОРОГИ, КОТОРАЯ ОБОРУДОВАНА ЗАЩИТНЫМИ ИНЖЕНЕРНЫМИ СООРУЖЕНИЯМИ
ОЦІНКА НЕБЕЗПЕКИ АВТОМОБІЛЬНОЇ ДОРОГИ, ЩО ОБЛАДНАНА ЗАХИСНИМИ ІНЖЕНЕРНИМИ СПОРУДАМИ
Keywords: highway; ingredient-parametric pollution; protective screen; risk assessment; dwelling zone; noise pollution; emergency situation; risk indexes; автомобильная дорога; ингредиентно-параметрическое загрязнение; защитный экран; автомобільна дорога; інгредієнтно-параметричне забруднення; захисний екран; 625.74; 504.3.054